KONSTRUKSI ILMU PENGETAHUAN DALAM PENDIDIKAN ISLAM : (Studi Pustaka Konsep Pendidikan Pada Kitab Kuning) - Afifuddin Ahmad Robbani; Ratu Vuna Rohmatika; M Kholis Amrullah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2022)
Scientific construction or the order of science certainly has some connection with some understanding of how a person seeks knowledge. Included in it will be touched on how the condition of the mind or physical when conducting the process of seeking knowledge, the factors that can support a person in sharpening his memory in seeking knowledge and several things that can cause a person's brain to easily forget the learning material. The purpose of this article is to re-emerge the concept of the order of science based on several classical books. The research methodology used is the method of literature review of Arabic-language books that discuss the order of science in education. The results of this literature review reaffirm that the authors of the classical book combined educational theory with the study of fiqh and morality.